A conceptual framework of the way forward to a community pharmacist- general practitioner collaborative medication therapy management model for chronic diseases in Malaysian primary care: a qualitative study - Mubarak, Naeem; Ali Raja, Sarwat; Sarwar Khan, Asma; Kanwa, Sabba; Saif-ur-Rehman, Nasira; Muhammad Majid, Aziz; Hussain, Irshad; Hatah, Ernieda; Zin, Che Suraya (Dove Medical Press, 2021)
Background There is a growing global interest in interprofessional collaboration between community pharmacist (CP) and general practitioner (GP) in primary care. Objective To conceptualize a stakeholder driven framework to improve collaboration between the CP and the GP in Malaysian primary care to effectively manage medicines in chronic diseases. Design and Setting A qualitative study that involved individual semi structured interviews of the leadership of various associations, guilds, and societies representing CPs, GPs, and Nurses in Malaysia. Method This study collected and reported data in accordance with the Consolidated Criteria for Reporting of Qualitative Studies guidelines. Key informants were recruited based on purposive (expert) sampling. Interviews were transcribed verbatim and data were coded in NVivo based on the principles of thematic analysis. Result A total of twelve interviews (5 CPs, 5 GPs and 2 Nurses) were conducted. Five themes emerged: Theme-1 highlighted comparison of community pharmacy practice in Malaysia and developed countries; Theme-2 involved the current practices in Malaysian primary care; Theme- 3 encompassed the advantages of CP-GP collaboration in chronic diseases; Theme-4 highlighted the barriers which impede collaboration in Malaysian primary care; and, Theme-5 delineated the way forward for CP-GP collaboration in Malaysia. Conclusion The actionable insights obtained from the Malaysian stakeholders offered an outline of a framework to enhance collaboration between CP and GP in primary care. Generally, stakeholders were interested in CP-GP collaboration in primary care and viewed many positive roles of CPs including prescription review, adherence support and patient education. The framework of the way forward includes: separation of roles of the CP and the GP through a holistic revision of relevant legislation to grant an active role to the CPs in chronic care; definition of protocols for collaborative practices; incentivization of both stakeholders (CP and GP) and, Design and implementation of an effective regulatory mechanism where the Malaysian Ministry of Health may take a leading role.